2011
DOI: 10.1111/j.1365-2427.2011.02696.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying relationships between land‐use gradients and structural and functional indicators of stream ecological integrity

Abstract: 1. Modification of natural landscapes and land-use intensification are global phenomena that can result in a range of differing pressures on lotic ecosystems. We analysed national-scale databases to quantify the relationship between three land uses (indigenous vegetation, urbanisation and agriculture) and indicators of stream ecological integrity. Boosted regression tree modelling was used to test the response of 14 indicators belonging to four groups -water quality (at 578 sites), benthic invertebrates (at 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
131
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(143 citation statements)
references
References 69 publications
(120 reference statements)
7
131
0
5
Order By: Relevance
“…Kail et al (2012) found thresholds of 16.3 % urban landuse in german catchments limiting ecological quality at the sites, Collier et al (2013) linked less than 20 % natural vegetation cover to changes in ecosystems functions and Death and Collier (2010) related the amount of catchment natural vegetation to water quality or biodiversity. However, in terms of biotic influences, land use can alter community composition and biodiversity patterns (Allan 2004;Harding et al 1998) and functional indices (Clapcott et al 2012;Collier et al 2013), but despite altering composition, this may not influence other environmental linkages including those between productivity, disturbance and diversity (Tonkin and Death 2012).…”
Section: Discussion Environmental Variablesmentioning
confidence: 99%
“…Kail et al (2012) found thresholds of 16.3 % urban landuse in german catchments limiting ecological quality at the sites, Collier et al (2013) linked less than 20 % natural vegetation cover to changes in ecosystems functions and Death and Collier (2010) related the amount of catchment natural vegetation to water quality or biodiversity. However, in terms of biotic influences, land use can alter community composition and biodiversity patterns (Allan 2004;Harding et al 1998) and functional indices (Clapcott et al 2012;Collier et al 2013), but despite altering composition, this may not influence other environmental linkages including those between productivity, disturbance and diversity (Tonkin and Death 2012).…”
Section: Discussion Environmental Variablesmentioning
confidence: 99%
“…We analysed metrics calculated using a range of regional and national datasets as described in Clapcott et al (2012). Metrics included water quality metrics (water visual clarity -Clarity, nitrate-N and nitrite-N concentration -NOx), macroinvertebrate metrics (Macroinvertebrate Community Index -MCI (average sensitivity score per taxon (Stark, 1985)), number of species producing once in a life cycle -Cycle), fish metrics (index of biological integrity -F-IBI (Joy and Death, 2004), percent of native fish species -Native) and ecosystem process metrics (ecosystem respiration -ER, gross primary production -GPP, cellulose decomposition potential -Cotton, δ 15 N of primary consumers -D15N).…”
Section: Methodsmentioning
confidence: 99%
“…measures that have been and can be widely adopted and communicated). We used a boosted regression tree (BRT) approach (Elith et al, 2008), to model the response of candidate metrics to land use and environmental gradients at a national scale as described in Clapcott et al (2011). A two-step model was developed where in the first step we examined the metric response to three land-use gradients: percentage of native vegetation cover remaining (VegR), percentage of impervious cover (IC), and the log-transformed predicted stream N concentration (LogN; based on landuse intensity whereby estimated nitrogen load is standardised by stream flow (Woods et al, 2006)).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations